The Gas Sector in Latin Europe's Industrial History: Lighting and Heating the World ed. by Ana Cardoso de Matos, Alexander Fernadez, and Antonio Jesús Pinto Tortosa (review). - Karampatsos, Christos (Technology & Culture, 2025)
The article provides an overview of "The Gas Sector in Latin Europe's Industrial History: Lighting and Heating the World," which examines the development of the gas industry in France, Spain, Portugal, and Italy from the late eighteenth century to 1945. The volume, resulting from a research project, emphasizes the role of French capital in spreading gas technology and presents a business and economic history perspective through ten articles. While it offers valuable insights into gas technology transfer and the industry's key figures, it is critiqued for lacking attention to labor issues and the broader societal impacts of gas technology. Overall, the work serves as a resource for historians interested in the gas sector's evolution in continental Europe.